Induction Therapy Prior to Surgical Resection for Patients Presenting with Locally Advanced Esthesioneuroblastoma - Miller, Kevin C.; Marinelli, John P.; Janus, Jeffrey R.; Chintakuntlawar, Ashish V.; Foote, Robert L.; Link, Michael J.; Choby, Garret; Van Gompel, Jamie J. (Journal of Neurological Surgery Part B: Skull Base, 2020)
Esthesioneuroblastoma (ENB) is a rare olfactory malignancy that can present with locally advanced disease. At our institution, patients with ENB in whom the treating surgeon believes that a margin-negative resection is initially not achievable are selected to undergo induction with chemotherapy with or without radiotherapy prior to surgery. In a retrospective review of 61 patient records, we identified six patients (10%) treated with this approach. Five of six patients (83%) went on to definitive surgery. Prior to surgery, three of five patients (60%) had a partial response after induction therapy, whereas two of five (40%) had stable disease. Microscopically margin-negative resection was achieved in four of five (80%) of the patients who went on to surgery, while one patient had negative margins on frozen section but microscopically positive margins on permanent section. Three of five patients (60%) recurred after surgery; two of these patients died with recurrent/metastatic ENB. In summary, induction therapy may facilitate margin-negative resection in locally advanced ENB. Given the apparent sensitivity of ENB to chemotherapy and radiotherapy, future prospective studies should investigate the optimal multidisciplinary approach to improve long-term survival in this rare disease.
Keywords: esthesioneuroblastoma; induction; therapy; neoadjuvant; outcomes